A benzothiadiazine derivative and methylprednisolone are novel and selective activators of transient receptor potential canonical 5 (TRPC5) channels. (September 2017) - Beckmann, Holger; Richter, Julia; Hill, Kerstin; Urban, Nicole; Lemoine, Horst; Schaefer, Michael
Graphical abstract: Highlights: New activators of transient receptor potential canonical 5 channels are presented. Methylprednisolone and the benzothiadiazine BTD selectively activate TRPC5 channels. BTD also activates heteromeric TRPC channel complexes containing TRPC5 subunits. Abstract: The transient receptor potential canonical channel 5 (TRPC5) is a Ca 2+ -permeable ion channel, which is predominantly expressed in the brain. TRPC5-deficient mice exhibit a reduced innate fear response and impaired motor control. In addition, outgrowth of hippocampal and cerebellar neurons is retarded by TRPC5. However, pharmacological evidence of TRPC5 function on cellular or organismic levels is sparse. Thus, there is still a need for identifying novel and efficient TRPC5 channel modulators. We, therefore, screened compound libraries and identified the glucocorticoid methylprednisolone and N-[3-(adamantan-2-yloxy)propyl]-3-(6-methyl-1, 1-dioxo-2H-1λ 6, 2, 4-benzothiadiazin-3-yl)propanamide (BTD) as novel TRPC5 activators. Comparisons with closely related chemical structures from the same libraries indicate important substructures for compound efficacy. Methylprednisolone activates TRPC5 heterologously expressed in HEK293 cells with an EC50 of 12 μM, while BTD-induced half-maximal activation is achieved with 5-fold lower concentrations, both in Ca 2+ assays (EC50 = 1.4 μM) and in electrophysiological whole cell patch clamp recordings (EC50 = 1.3 μM). The activation resulting from both compounds is long lasting, reversible and sensitive to clemizole, a recently established TRPC5 inhibitor. No influence of BTD on homotetrameric members of the remaining TRPC family was observed. On the main sensory TRP channels (TRPA1, TRPV1, TRPM3, TRPM8) BTD exerts only minor activity. Furthermore, BTD can activate heteromeric channel complexes consisting of TRPC5 and its closest relatives TRPC1 or TRPC4, suggesting a high selectivity of BTD for channel complexes bearing at least one TRPC5 subunit.